In the Wake of the Holocaust: Massimo Vitale, Pius XII, and the Battle over the Good Friday Prayer for the “Perfidious Jews” - Kertzer, David I.; Benedetti, Roberto (Studies in Christian-Jewish Relations, 2023)
While the Good Friday prayer, with its reference to perfidis Judaeis, had long been a source of unhappiness in the Jewish community, the Holocaust triggered new efforts to have it changed. The recent opening of the Vatican archives for the papacy of Pius XII (1939-1958) now permits a much fuller understanding of these pressures and how the pope and those around him dealt with them. The newly available Vatican documents, together with records from Italian Jewish organizational archives, highlight the key role in this campaign played by Massimo Adolfo Vitale, leader of Italian Jewry’s efforts to determine the fate of the thousands of Jews who had been deported to Nazi concentration camps in the war. The case offers insight as well into the larger question of how the Vatican confronted the legacy of the Holocaust.